Early derangement of INR predicts liver failure after liver resection for hepatocellular carcinoma. Issue 5 (October 2022) - Silva, A.N.S.; Greensmith, M.; Praseedom, R.K.; Jah, A.; Huguet, E.L.; Harper, S.J.F.; Liau, S.S.; Basu, B.; Alexander, G.J.; Brais, R.; See, T.C.; Hoare, M.; et al.
Abstract: Background: Surgical resection, where appropriate, remains one of the best treatment options for hepatocellular carcinoma (HCC), however outcomes can be compromised by the development of liver failure. We reviewed our experience of liver resection for HCC patients to identify factors that may predict the development of post-hepatectomy liver failure (PHLF) and survival. Methods: A single centre retrospective cohort study. Data was collected between 1999 and 2017 from all patients undergoing HCC resection in a tertiary university hospital from electronic medical records. PHLF was defined as per the International Study Group for Liver Surgery criteria. Variables with p < 0.15 on univariate analysis were included in a multivariate binary logistic regression model. Kaplan–Meier analyses were used to determine correlations with overall survival (OS) and disease-free survival (DFS), and variables with p < 0.15 on univariate analysis selected for a step-down Cox proportional hazard regression model. Results: Overall, 120 patients underwent liver resection within the study period, of which 22 (18%) developed PHLF. Patients with normal INR ≤1.20 at day 2 did not develop PHLF whereas patients with INR >1.60 were at significant risk. Resection of multiple tumours (odds ratio 21.63, p = 0.002) and deranged postoperative day 2 INR>1.6 (odds ratio 21.05, p < 0.0001) were identified as independent prognostic markers of PHLF. Conclusion: The use of INR measurement at day 2 predicts PHLF and may enable us to objectively identify and stratify patients who may be eligible for enhanced recovery programs from those who will merit close monitoring in high dependency areas. Graphical abstract: Image 1 Highlights: Postoperative day 2 INR stratifies the risk post-hepatectomy liver failure (PHLF) Postoperative day 2 INR ≤1.20 predicts absence of PHLF Postoperative day 2 INR >1.6 increases the risk of PHLF 95% of patients with major complications had INR >1.20 at postoperative day 2